Association Between Dietary Patterns of Salty Foods, Sweet Drinks, Fruit and Vegetables and The Prevalence of Hypertension in East Java: Multivariate Analysis of Indonesian Basic Health Surveys Data 2018 - Andrianto; Mohammad Satya Bhisma; Fita Triastuti; Budi Susetyo Pikir; Annisa Trissatharra (Media Gizi Indonesia, 2023)
Hypertension remains the main cause of mortality globally, including in Indonesia, with a prevalence rate of 34.1%. Various studies have reported an association between dietary patterns and the prevalence of hypertension. Therefore, further analysis is needed to determine preventive intervention strategies in each region. This study aimed to analyze the effect of dietary patterns on the prevalence of hypertension in East Java Province. The sample is the result of multistage random sampling from the census block of Basic Health Research (Riskesdas) report in the East Java Province collected from 2013 – 2018. The classical assumption test was carried out using the Kolmogorov-Smirnov method, bivariate test using the Pearson method, and multivariate test using the multiple linear regression method. There are three variables tested that have a p-value below the value of α <0.05, including eating salty foods once a day (p=0.021), drinking sweet drinks three times per month (p=0.008), and non-routine of fruits and vegetables consumption (p=0.003). Based on the r-value, the association between predictor variables and prevalence in order from the largest to the smallest of the habit of not consuming fruits and vegetables (r=-0.469), the habit of drinking sugary drinks three times per month (r=-0.425), and salty eating habits one time per day (r=-0.372). Multivariate multiple linear regression analysis showed that daily intake of salty foods (p=0.013) was associated with the prevalence of hypertension.